CSR as Value Attunement within Governance Processes: Stakeholder Dialogue, Corporate Principles and Regulation. (8th September 2016) - de Graaf, Frank Jan
Abstract: I argue that a governance perspective on corporate social responsibility (CSR) makes it possible to explain why the concept will always be under‐defined, is normative and thus political by nature, and is and should be difficult to measure. The perspective also makes it possible to understand the interaction between corporate values and stakeholders values. In processes of dialogue within governance systems and governance structures, changing insights into the principles of CSR can lead to regulation or its adjustment. Power is important in these dialogues. Principles are at least partly shaped within governance systems and governance structures, and they influence the outcomes of corporate policies. Changes within the regulatory framework could also lead to changes in the principles of CSR. Value attunement processes could lead to regulation, which again influences the governance structures and thus the power of stakeholders within the dialogue. The theoretical model provided helps to analyze why CSR is different in companies, cultures and academic traditions.